Pelatihan Memahami Fiqih Praktis Melalui Pembelajaran Kitab Fathul Qarib Di Pondok Pesantren Alif Lam Mim - Ghulam Akhyar Rikza; Rifani Raniasati; Muhammad Maskur Musa; Amma Chorida Adila; Elsa Tiara; Inayah Priyatun; Ayu Febriyanti; Teguh Handoyo; Ana Chonitsa; Siti Salamah; Adinda Riski Amalia; Hendri Hermawan Adinugraha (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2022)
F Fiqh has a very broad scope of study and has high urgency. Unfortunately, many of the younger generation neglect and even underestimate the basic laws of fiqh, such as procedures for purification, prayer procedures, and others. A human being will certainly feel the need for fiqh along with his awareness as a Muslim, especially for a student who is an agent of change and is seen as intellectuals. This training aims to increase students' understanding and awareness of practical fiqh through studying the book of Fathul Qarib. The learning method carried out in this activity is using the bandongan method, and asking the bandongan method is a method in teaching the yellow book in which the kyai or ustadz reads, translates and explains the yellow book, then students listen and write the translation (ngapsahi). While the question and answer method is a method that is also carried out by providing opportunities to ask questions in accordance with the chapters discussed in the study of the Fathul Qarib book, the question and answer method is carried out after the bandongan.answer method. Based on the results of the Fathul Qarib training activities at the Alif Lam Mim Islamic boarding school, it can be concluded that. students can evaluate themselves regarding their understanding of practical fiqh. The students can also add and improve knowledge and understanding of the science of fiqh. From this learning, the students can apply the science of fiqh in everyday life correctly and in accordance with existing laws.